Penanggulangan Tindak Pidana Cyber Terrorism dalam Perspektif Kepastian Hukum - Indrawan, Arvid Gema; Semendawai, Abdul Harris; Wiryanto, Wiryanto (Fakultas Hukum, Universitas Islam As-Syafi'iyah, 2021)
One example of the Cyber ​​terrorism case committed by Bahrumsyah and M. Bahrun Naim, who is known to have transferred funds to make car bombs to ISIS support groups in Solo. So based on the crimes committed by Bahrun in getting money from the ISIS group in Syria, while the money sent to his network in Indonesia was carded. The main problem of this research is law enforcement in the prevention of cyber terrorism according to Indonesian positive law, and the legal provisions for tackling cyber terrorism from the perspective of legal certainty. This research is included in the normative juridical research typology with secondary data types, so as to produce research in the form of prescriptive analytical through literature studies. The results of this study reveal that there is no law enforcement in the prevention of cyber terrorism. Theoretically, the perpetrators of cyber terrorism cannot be held accountable because criminal liability takes into account the elements against the law in the formulation of offenses and is related to the principle of legality and elements of guilt. The lack of certainty in tackling cyber terrorism is due to the higher frequency of technology use with a developing system, with the existing convergance of media. It is hoped that it can provide legal certainty that comprehensively regulates the movement and use as well as irregularities in cyber crime that uses computers as the main tool and benefits of the developing technological media